The use of computers in the teaching of english in SK St. Teresa, SK St Patrick Tangga, SK Serian and SK Tanah Merah, Serian/ Ungau Alam - Alam, Ungau (2007)
This study aims to highlight various issues pertaining to the level of literacy in the use of computers by the teachers in the language classrooms with specific reference to the teaching of English in SK St. Teresa, SK Tangga, SK Serian and SK Tanah Merah respectively. The study focuses on teachers’ content knowledge and their ability to use computers effectively as well technical constraints faced during the course of language classroom instruction. Based on the responses to the questionnaires, it is revealed that most of the respondents still lack the knowledge about computing, whilst the use of computers in classroom instructions is very minimal. Since the scope of study is limited to just four schools, the findings can in no way represent the present scenario of the application of computers in the classroom in other schools particularly in Serian District and the country as a whole. However, it is hoped that the findings might trigger similar and broader research to be conducted on similar field of studies.